ANALYSIS OF SEASONAL LEVELS OF ATMOSPHERIC POLLUTION IN TERENGGANU, MALAYSIA - Ahmad, H. I.; Mustapha, A.; Juahir, H.; Alhaji, M.; Adamu, H. (FUDMA JOURNAL OF SCIENCES, 2023)
This study aims to investigate the seasonal fluctuation in the level of air quality, determine the most discriminating parameters in each season and identify the possible sources of pollution over a period of 13years (1999-2011). Two monsoon seasons (northeast and southwest monsoon) were selected because of their difference in formation, time of occurrence and climatic characteristics. The air quality and meteorological observation data such as particulate matter (PM10), carbon monoxide (CO), nitrogen dioxide (NO2), sulfur dioxide (SO2), ozone (O3), ambient temperature and wind speed for a period of thirteen years (1999-2011) were obtained from Department of Environment Malaysia (DOE). The results revealed that, the Discriminant Analysis (DA) provided better results with great discriminatory ability using six (6) parameters (p < 0.05) with a correct assignation of 82.13%. Further, Principal Component Analysis (PCA) for the northeast and southwest monsoon accounted for more than 51% and 61.40% of the total variance respectively. The sources of pollutants for both seasons are from anthropogenic activities and natural factors (point and non-point sources). The bar chart plotted for each season show that atmospheric air pollutants reaches maximum level during the southwest monsoon season and drops during the northeast monsoon. Multivariate technique serves as a tool for understanding the seasonal variation in air pollution. These findings can be used for planning and policy making by stakeholders by re-enforcing the Malaysian air quality standard.